A polar confidence curve applied to Fieller's ratios - Halvor Mehlum (University of Oslo, Department of Economics, 2017)
I derive the polar representation of Fieller's estimation of confidence sets for ratios and construct a polar plot of the test statistics for all angles associated with the ratios. This procedure helps in visualizing and clarifying, but also systematizing, the features of the Fieller solution. In conclusion I discuss, using Ramanujan, the case where Fieller's method yields a confidence set covering the entire real line.
Keywords: C30; 330; Confidence curve; Fieller solution; test